ASSESMENT OF THE INJURIES CAUSED BY SHARP INSTRUMENTS IN THE HEALTH WORKERS OF UNIVERSITY HOSPITALS, IN YAZD - H. Nazmieh; A. Najaf-Yarandi; S. Janmohammadi; F. Hosseini (Iran University of Medical Sciences, 2005)
Today, injuries caused by sharp instruments and needle sticks are one of the most important and serious biological threats among caregivers. The injuries might cause the ease of transmission of fatal diseases such as AIDS and hepatitis B and C.   The aim of this study was investigating the frequency and characteristics of the injuries and protective measures in caregivers.   The research design was a descriptive study in which a questionnaire was used to gather the data. The study sample consisted of all staff of medical team of selected three hospitals in yazd.   The result showed that 38.7% of the subjects stated that, they had experienced the injuries within the past 6 months prior to the study. There were significant statistical correlations between the variables of the injuries with age, as well as the injuries with occupational groups and work settings (P=0.04, 0.000 and 0.000) respectively. According to the results, it was found that the most threatening unit was emergency ward (53.6%). The most dangerous instrument were needles (79.9%) and the most hazardous procedure, were injections (47.6%). Sixty percent of the subjects suggested not putting latex gloves on during medical procedures and 7.9% of the staff have not been recapped the disposable needles. About 44.2% of the subjects, suggested that they compressed the injury sites to reduce bleeding and 23.6% had reported the accident verbally.   According to the study findings, providing educational sessions regarding safe injections, appropriate written reporting of the accidents, general percussions (put gloves on, recapping needles) and immediate appropriate interventions after occurrence of the injuries, are strongly recommended.